2020
DOI: 10.1542/peds.2020-002725
|View full text |Cite
|
Sign up to set email alerts
|

Group Sessions or Home Visits for Early Childhood Development in India: A Cluster RCT

Abstract: Poor early childhood development in low-and middle-income countries is a major public health problem. Efficacy trials have shown the potential of early childhood development interventions but scaling up is costly and challenging. Guidance on effective interventions' delivery is needed. In an open-label cluster-randomized control trial, we compared the effectiveness of weekly home visits and weekly mother-child group sessions. Both included nutritional education, whose effectiveness was tested separately.METHOD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 26 publications
5
44
1
3
Order By: Relevance
“…Furthermore, the lack of statistically significant subgroup results by program duration, delivery modality, and setting are also consistent with the few prior meta-analyses that have conducted similar analyses and shown no associations between these program aspects and intervention effects on ECD and parent-level outcomes [62]. One recently published cluster RCT specifically compared the effectiveness of weekly home visits to weekly mother-child group sessions over a 2-year period in rural India [64]. Trial results revealed that group sessions were as effective as home visits in improving child cognition and language, and both delivery models similarly had null impacts on child motor, socioemotional, behavior development, and parenting knowledge and practices.…”
Section: Plos Medicinesupporting
confidence: 79%
“…Furthermore, the lack of statistically significant subgroup results by program duration, delivery modality, and setting are also consistent with the few prior meta-analyses that have conducted similar analyses and shown no associations between these program aspects and intervention effects on ECD and parent-level outcomes [62]. One recently published cluster RCT specifically compared the effectiveness of weekly home visits to weekly mother-child group sessions over a 2-year period in rural India [64]. Trial results revealed that group sessions were as effective as home visits in improving child cognition and language, and both delivery models similarly had null impacts on child motor, socioemotional, behavior development, and parenting knowledge and practices.…”
Section: Plos Medicinesupporting
confidence: 79%
“…Child development scores, as assessed by the ASQi and CDI were higher in both intervention arms when compared with the control, with differences for 6 of the 7 domains significant for the group arm, but not for the combined arm. Differences in standardised child development scores for the group intervention arm are between 0.18 to 0.39, similar to those from a group intervention in rural India which found significant improvements in cognition scores of 0.28 SDs, 28 and an integrated home visiting programme in rural China, with intervention effects of 0.24 SDs. 13 The results from a supplementary analysis on a subset of participants demonstrate improved receptive communication and total Bayley-III scores among those who received any intervention compared with the control.…”
Section: Discussionsupporting
confidence: 68%
“…Though the current study was not powered to compare the group and combined arms directly, recent work from rural India finds similar effects on child development outcomes from group and individual home-based sessions. 28 Further, recent work from rural Kenya indicates that group sessions may outperform combined delivery in some settings. 29 Our work supports the delivery of multicomponent, mixed-age group sessions to improve risk factors for poor child development in rural Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 These evaluation efforts require instruments to measure ECD that are feasible for use in a wide range of survey conditions, particularly for children under the age of 3 years. 1,7,8 However, many of the frequently used diagnostic instruments, such as the Bayley Scales of Infant Development, 9 while reliable 8,10 and sensitive to differences due to interventions, [11][12][13] are designed for use by clinically trained professionals in specific contextsprimarily high-income and westernized 14 -and are difficult and expensive to adapt to field settings in low-income environments. 15 Moreover, most of these tests are proprietary, involving expensive test kits and administration fees (copyrights), and their administration is long and requires the presence of the child-all of which makes them impractical for use at large scale.…”
Section: Introductionmentioning
confidence: 99%